2021
DOI: 10.1002/jez.2498
|View full text |Cite
|
Sign up to set email alerts
|

Sperm motility analysis of Cobitis hankugensis, Iksookimia longicorpa (Teleostei, Cypriniformes, Cobitidae) and their unisexual natural hybrids

Abstract: Hybrid sterility is an inevitable phenomenon in the speciation process to avoid indiscriminate increases in species, but it is not always unconditional. We used computer assisted sperm analysis (CASA) to analyze sperm motility of Cobitis hankugensis, Iksookimia longicorpa, and their unisexual natural hybrids. In parental species, the sperm concentrations of C. hankugensis and I. longicorpa were 11.6 ± 4.8 × 10 9 and 16.5 ± 6.8 × 10 9 , respectively. For sperm motility, the total motility was higher in the pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Nevertheless, on gonadal tissue fragments, we observed only rare spermatid and sperm cells, which matches previous histological observations showing the presence of malformed spermatids of various sizes and a high number of apoptosis (Park et al, 2011). Interestingly, rare sperm were earlier found in triploid hybrid males, albeit with significantly decreased motility compared to parental species (Yun et al, 2021). This somewhat corresponds to our finding of clusters of spermatocytes in metaphase I with aberrant chromosome attachments to the spindle, possibly due to univalent and multivalent formation during meiosis I.…”
Section: Pairing Of Orthologous Chromosomes Is Aberrant and Cause Ste...supporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, on gonadal tissue fragments, we observed only rare spermatid and sperm cells, which matches previous histological observations showing the presence of malformed spermatids of various sizes and a high number of apoptosis (Park et al, 2011). Interestingly, rare sperm were earlier found in triploid hybrid males, albeit with significantly decreased motility compared to parental species (Yun et al, 2021). This somewhat corresponds to our finding of clusters of spermatocytes in metaphase I with aberrant chromosome attachments to the spindle, possibly due to univalent and multivalent formation during meiosis I.…”
Section: Pairing Of Orthologous Chromosomes Is Aberrant and Cause Ste...supporting
confidence: 90%
“…Genomic composition and the type of ploidy of every investigated specimen were firstly evaluated using the morphological examination of external characters and size of red blood cells (Ko, 2009;Park et al, 2011;Yun et al, 2021) followed by PCR-sequencing of a speciesdiagnostic nuclear gene, enc 1 (ectodermal-neural cortex I), and mitochondrial cyt b gene (cytochrome b) according to previous genetic studies involving the two species (Kwan et al, 2018;Kwan et al, 2019). In other words, the ploidy level and genomic composition of each fish examined for the cytogenetic study were determined by combining two complementary methods: size measurement of erythrocytes (Ko, 2009) and DNA sequencing of the enc 1 gene.…”
Section: Species and Ploidy Identificationmentioning
confidence: 99%
“…Nevertheless, on gonadal tissue fragments, we observed only rare spermatid and sperm cells, consistent with previous histological observations showing the presence of malformed spermatids of various sizes and a high degree of apoptosis 45 . Interestingly, rare sperm were found in triploid hybrid males, although they exhibited significantly reduced motility compared to parental species 46 . It corresponds to our finding of clusters of spermatocytes in metaphase I with aberrant chromosome attachments to the spindle, possibly due to univalent and multivalent formation during meiosis I.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) 37 , 38 , 44 . Despite the differences in chromosomal number 37 , 38 , 44 , morphology, and the number of species-specific genetic markers 41 , 45 , 46 , the recognition of parental genomes is highly important in the hybrids. Previous crossing experiments, followed by the analysis of ploidy, morphology, and karyotypes of progenies, suggested that diploid hybrid females produced diploid eggs 41 , 43 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation